2015
DOI: 10.5539/gjhs.v7n5p364
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Carrier Thalassemia Marriage Volunteer in Prevention of Major Thalassemia

Abstract: Introduction:Thalassemia is the most common genetic disorder and rising in the world as a health problem. Due to the criticality of this disease, in our country thalassemia prevention programs are more importance. The aim of this study was investigation of knowledge, attitude and behavior of marrying partners who were thalassemia genetic carriers in prevention of the birth of the children with major thalassemiaMethods:This study was a descriptive-analytic study. Data collection tool was a self-administered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…The importance of having high knowledge and participation levels in screening for thalassemia in other groups has been described by a few studies. Almost half of the participants in a study in Iran believed that increasing knowledge was the most vital step to preventing thalassemia, along with genetic counselling and premarital screening (15). Thalassemia education in Cambodia, even in populations with low education levels, was shown to increase knowledge and promote positive attitudes towards screening (16).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of having high knowledge and participation levels in screening for thalassemia in other groups has been described by a few studies. Almost half of the participants in a study in Iran believed that increasing knowledge was the most vital step to preventing thalassemia, along with genetic counselling and premarital screening (15). Thalassemia education in Cambodia, even in populations with low education levels, was shown to increase knowledge and promote positive attitudes towards screening (16).…”
Section: Discussionmentioning
confidence: 99%
“…22 Similarly study conducted at Iran reported that only 20% participants had knowledge regarding hereditary nature this disorder. 23 Another study from Lahore reported that 44.6% participants knew that thalassemia is genetic disorder. 24 This issue needs to be addressed as these results suggest that parents don't have adequate knowledge regarding thalassemia and its mode of inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…Pengetahuan thalassemia di Indonesia belum sepenuhnya diteliti secara intensif, datadata penelitian mayoritas masih banyak berkutat pada masalah kuratif atau rehabilitatif pasien. Hal serupa juga terjadi pada negara berkembang lainnya seperti Malaysia 14 , Pakistan 15 , Iran 16 dan India. 17 Pengetahuan masyarakat tentang thalassemia pada tingkat perifer masih sangat minim, bahkan pada kalangan berpendidikan tinggi.…”
Section: Pembahasanunclassified